Clinical predictors of left ventricular thrombus after myocardial infarction as detected by magnetic resonance imaging - Fardman, Alexander; Massalha, Eias; Natanzon, Sharon Shalom; Brodov, Yafim; Goitein, Orly; Chernomordik, Fernando; Herscovici, Romana; Grupper, Avishay; Kuperstein, Rafael; Mazin, Israel; Matetzky, Shlomi; Beigel, Roy (Frontiers in Cardiovascular Medicine, 2024)
The diagnosis of a left ventricular (LV) thrombus in patients with ST segment elevation myocardial infarction (STEMI) remains challenging. The aim of the current study was to characterize clinical predictors for LV thrombus formation, as detected by cardiac magnetic resonance imaging (CMRI).We retrospectively evaluated 337 consecutive STEMI patients. All patients underwent transthoracic echocardiography (TTE) and CMRI during their index hospitalization. We developed a novel risk stratification model (ThrombScore) to identify patients at risk for development of a LV thrombus.Upon CMRI, LV thrombus was present in 34 patients (10%), of whom 33 (97%) had an anterior wall MI, and most (77%) had at least mildly reduced left ventricular ejection fraction (LVEF<45%). Sensitivity for thrombus formation of the first and second TTE was 5.9% and 59%, respectively. Multivariate logistic regression model revealed that elevated C-reactive protein levels, lack of ST-segment elevation (STe) resolution, elevated creatine phosphokinase levels, and STe in anterior ECG leads are robust independent predictors for the development of a LV thrombus. These variables were incorporated to construct the ThrombScore: a simple sixpoint risk model. The odds ratio for thrombus development per one-point increase in the score was 3.2 (95% CI 2.1-5.01; p<0.001). Discrimination analysis of the model revealed c-statistics of 0.86 for thrombus development. The model identified three distinct risk categories (I, II and III) with thrombus incidence of 0%, 1.6% and 27.6%, respectively.ThrombScore is a simple, practical, clinical model for risk stratification of thrombus formation in patients with STEMI.